Hypopigmentation in dark skin: a diagnostic challenge. - Silva, J.S.; Pereira, M.I.; Gorito, V.; Quaresma, M. (European Journal of Pediatric Dermatology, 2026)
We report a 4-month-old dark-skinned male infant who presented with generalized pruritic, hypochromic, and scaly lesions initially suspected to represent depigmentation of unknown origin. Dermatologic evaluation revealed atopic dermatitis (AD) with post-inflammatory hypopigmentation. The infant responded favorably to topical corticosteroids and emollients. This case illustrates the diagnostic challenges of AD in infants with dark skin, where atypical color changes may mask underlying inflammation, leading to delayed recognition and treatment.